THE INFLUENCE OF FINANCIAL RATIOS AND MATURITY DATES ON BOND RATINGS CHANGES IN FINANCIAL INDUSTRIES OF THE INDONESIA STOCK EXCHANGE - Setiawan, Chandra; Permata, Cinta (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
A bond rating is an important indicator in fixed-income securities that significantly assesses. The relationship between financial ratios and maturity dates with changes in bond ratings is very important. It provides valuable insights into the issuer's financial health and ability to repay debts within the specified tenor. This research investigates information related to the effect of financial ratios and maturity dates on changes in bond ratings in the Indonesia Stock Exchange using Panel Data Regression for 2017-2022. The result of this study is that maturity date has a negative effect on changes in bond ratings, current ratio does not affect changes in bond ratings, return on asset has a negative effect on changes in bond ratings, the net profit margin has a positive effect on changes in bond ratings, and debt to equity has a positive effect on bond ratings in Indonesia Stock Exchange (IDX). Before investing, investors should look at the bond-issuing company’s financial ratios and bond ratings to get better returns. This study aims to provide a deeper understanding of the credit rating process, help investors make more informed investment decisions, and contribute to the efficient functioning of the Indonesian bond market.